The effect of attenuating noradrenergic neurotransmission by clonidine on brain activity measures of visuospatial attention. (12th November 2013) - Logemann, H. N. Alexander; Böcker, Koen B. E.; Deschamps, Peter K. H.; Kemner, Chantal; Kenemans, J. Leon
<x xml:space="preserve">Abstract</x> Objective In the current study, we investigated the role of noradrenaline in directing (bias) and disengagement of visuospatial attention. Methods We assessed the effect of clonidine on event‐related brain potential (ERP) reflections of bias and disengagement in a double‐blind placebo‐controlled crossover design. An initial dose of 200‐µg clonidine was replaced by 100 µg because of marked side effects. Twenty‐one healthy male participants performed the visual‐spatial cueing task while an electroencephalogram (EEG) was recorded. The behavioral output is the validity effect (benefit of cueing in terms of reaction time to targets). ERP indices for bias were the cue‐related early directing attention negativity and late directing attention positivity, and the target‐elicited P1 and N1 modulations by validity ('validity‐effect'). The ERP index for disengagement was the target‐elicited 'late positive deflection' modulation by validity. Behavioral analyses were performed on 16 participants, electrophysiological analyses on a subset (n = 9). Results Clonidine attenuated the N1 effect, albeit in a subsample. Neither cue‐elicited ERPs nor the behavioral validity effect were affected. Clonidine‐induced blood pressure reduction was correlated with the reduction of the late positive deflection effect under clonidine. Conclusion Clonidine attenuated the result of bias in a subsample and may have a modulating effect on disengagement. Copyright © 2013 John Wiley & Sons, Ltd.